ORIGINAL ARTICLEClinical characteristics and treatment strategies in patients with acute coronary syndromes in hospitals without an on-site invasive facility. The Registry of Acute Coronary Syndromes in the Malopolska Region 2002-2003 - Dudek, Dariusz; Siudak, Zbigniew; Kuta, Marcin; Mielecki, Waldemar; Rakowski, Tomasz; Dziewierz, Artur; Giszterowicz, Dawid; Dubiel, Jacek S. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Introduction: Acute Coronary Syndromes (ACS) are divided, based on the ECG curve, into ST segment Elevation Acute Coronary Syndromes (STE ACS) and Non ST segment Elevation Acute Coronary Syndromes (NSTE ACS). The aim of this study was to assess clinical and demographic characteristics of the STE ACS and NSTE ACS patients as well as adherence to current ACS treatment guidelines in hospitals without an on-site invasive facility. Methods: The analysed data come from the Registry of Acute Coronary Syndromes in the Malopolska Region. Twenty nine hospitals, 7 from the Krakow City and 22 from the Malopolska Region, took part in the registry. Data were gathered in between April 2002 and February 2003. Patients were divided according to the initial diagnosis: NSTE ACS or STE ACS. Results: Data on 2382 patients were gathered. STE ACS was diagnosed in 45% (1059) of the patients, whereas NSTE ACS in 55% (1323 patients). An invasive approach was undertaken in 13,9% of STE ACS and 14,4% of NSTE ACS patients (p=NS). In-hospital mortality among the patients remaining in community hospitals for conservative treatment was 12% in STE ACS and 1,9% in NSTE ACS patients respectively (p<0.0001). STE ACS patients more frequently received GP IIb/IIIa inhibitors (4% vs 0,7%; p<0.0001). The lytic therapy was administered in only 20.7% of all STE ACS patients. Conclusions: NSTE ACS patients account for more than half of all ACS patients. Despite the 24-hour availibility of invasive treatment, only a small number of patients is transferred for invasive diagnostics and treatment. Patients with conservative treatment regimen, in community hospitals without an on-site invasive facility, experience high in-hospital mortality. It seems necessary to create networks of community hospitals cooperating with invasive facility centres which will eventually result in an increase of patients transferred for angiography. This should be beneficial in the subgroup of high risk ACS patients.